Effectiveness of Various Chlorhexidine-Based Insertion Site Protocols in Preventing CRBSI among Hemodialysis Patients: A Systematic Review and Synthesis Without Meta-analysis (SWiM) - Sri Hariyanti; Yulia Yulia; Dikha Ayu Kurnia (Indonesian Journal of Global Health Research, 2026)
Chronic Kidney Disease (CKD) is a global health issue affecting 10–15% of the world's population, often progressing to End-Stage Renal Disease (ESRD). Hemodialysis (HD) is the primary renal replacement therapy; however, the use of a Central Venous Catheter (CVC) for vascular access increases the risk of Catheter-Related Bloodstream Infections (CRBSI). Skin pathogens such as Staphylococcus aureus account for 40–80% of CRBSI cases, contributing to increased morbidity and mortality. The use of chlorhexidine (Chlorhexidine Gluconate/CHG) at the insertion site aims to inhibit extraluminal bacterial colonization. However, the effectiveness of various CHG protocols remains a subject of debate due to the risk of contact dermatitis and cost-effectiveness. This systematic review aims to evaluate the effectiveness of various chlorhexidine-based insertion site care protocols in preventing CRBSI events in hemodialysis patient. This systematic review was conducted in accordance with the PRISMA 2020 guidelines, using the “Synthesis Without Meta-analysis” approach, and is registered with PROSPERO 2026 under CRD420261368887. A search was conducted in the EBSCO, PubMed, Sage Journals, ScienceDirect, Scopus, and Wiley databases using the keyword “chlorhexidine-based catheter insertion care for the prevention of CRBSI.” Articles published between 2010 and 2025 were searched, resulting in a total of 1,412 articles identified from the initial database search.. A total of 7 articles meeting the inclusion criteria, consisting of RCTs and quasi-experimental studies. The outcomes analyzed included catheter-related infections such as CRBSI, CLABSI, and CRI. The direction of effects was analyzed narratively, and study quality was assessed using RoB 2 and JBI. Four studies showed a reduction in the incidence of infection, while three studies showed no significant difference. No increased risk of infection was found in any of the studies. Most studies used chlorhexidine sponges or patches (4 studies, 57%); 28% used chlorhexidine-impregnated dressings; and the remainder used chlorhexidine solution. Most studies were of moderate to good quality, with some potential for bias. Three studies showed p-values < 0.05. Chlorhexidine-based care protocol interventions show a tendency to reduce catheter-related infections in hemodialysis, but results remain inconsistent. The implementation of evidence-based nursing practices, particularly tailored to tunneled and non-tunneled catheters, is necessary to optimize infection prevention.